Pengaruh Leverage, Profitabilitas, dan Firm Size Terhadap Ketepatan Waktu Pelaporan Laporan Keuangan: Studi Empiris Pada Perusahaan Food and Beverages yang Terdaftar di BEI Periode 2019-2023 - Dara Cyntya Putri; Munari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to obtain empirical evidence regarding the influence of leverage, profitability and firm size variables on the timeliness of reporting financial reports in food and beverages subsector companies listed on the IDX for the 2019-2023 period. This type of research is quantitative research. The data used in this research is secondary data. The population in this research is food and beverages subsector companies registered on the IDX for the 2019-2023 period, namely 84 companies. The sample in this research was 28 companies that met the researchers' criteria, so a total of 140 samples were obtained over 5 years of research. The sampling technique uses purposive sampling technique. The data analysis used is logistic regression analysis using SPSS version 25 software. From the research conducted, the results obtained are that the leverage variable has no effect on the timeliness of financial report reporting, while the profitability and firm size variables have an effect on the timeliness of financial report reporting, as well as the variables leverage, profitability, and firm size simultaneously influence the timeliness of reporting financial statements.